Governance related corporate climate change disclosures: evidences from selected public listed companies in Malaysia - Nik Ahmad, Nik Nazli; Hossain, Dewan Mahboob (2017)
The study was undertaken in two phases. In phase one, we explored the nature of governance related climate change reporting in the annual reports and sustainability reports of selected public listed companies in Malaysia. We first conducted a content analysis of the annual reports and sustainability reports of the sample companies, to identify (i) whether these companies report on governance related climate change issues and (ii) if they report on these issues, what do the companies report. Next, we examine how these companies are reporting on climate-change issues using a rhetorical analysis of the language of the governance related climate change disclosures. In phase two, we examined the extent and nature of climate change-related governance information disclosed by companies short-listed for the ACCA MaSRA 2016 (ACCA Malaysian Sustainability Reporting Awards 2016). We also examined how language is used in the corporate narratives to enhance corporate legitimacy and manage stakeholders’ impressions.